Perception and Understanding of Climate Change and Its Impact in Gandaki River Basin, Central Himalaya, Nepal - Basanta Paudel; Prem Sagar Chapagain; Shobha Shrestha; Yili Zhang; Linshan Liu; Jianzhong Yan; Suresh Chand Rai; Md. Nurul Islam; Tibendra Raj Banskota; Khagendra Raj Poudel; Keshav Raj Dhakal (Atmosphere, 2022)
Climate change is a global issue. Its impacts are recognized at different scales ranging from global to regional to local. Climate change particularly changes in temperature and precipitation has been observed differently in different ecological regions in Nepal Himalaya. The study area comprises five villages of three ecological regions in the Gandaki River Basin (GRB) of Nepal. Based on the observed climate data of a 30-year period from 1990 to 2020, the changes in temperature and precipitation of each ecological region are analyzed using the Mann–Kendall trend test and Sen’s slope. The temperature trend was found to be increasing at the rate of 0.0254 °C per year (°C/a) between 1990 and 2020 in the Mountain region, by 0.0921 °C/a in the Hill region and 0.0042 °C/a in the Tarai region. The precipitation trend in the Mountain region is decreasing by −13.126 mm per year (mm/a), by −9.3998 mm/a in the Hill region and by −5.0247 mm/a in the Tarai region. Household questionnaire surveys, key informant interviews and focus group discussions were carried out to assess the perception of climate change and its impact. The farmers of the three ecological regions have perceived increasing temperature trends, but perceived variability in precipitation trends. Both snowfall and rainfall have varied. Snowfall has drastically decreased. Drought has increased. Extreme disaster events and impacts from such climate-induced events are experienced by 67.9% of respondents. A major impact of climate change is reported on cultivated crops with damage caused by increased insect and rodent pests. The impact of climate change is varied by ecological region. The comparative study of observed data and household data shows the need for a micro-level study so that a real situation can be captured and would be very much useful for policy formulation to combat climate change at a local scale.